Population Engineering on Dynamic Process of Migration and Demographic Processes in Kazakhstan - Kunduzai Myrzashnovna, Yerimbetova; ., . (International Journal of Engineering and Technology, 2018)
Modern migration is a dynamic and complex social phenomenon. It is characterized by significant scale and diversity, due to a complex of factors: socio-economic, political, ethnic, religious, environmental, demographic and others. The article reveals the demographic processes of the Republic of Kazakhstan, its specific features, characteristics, and development factors, as well as mechanisms for regulating internal migration, its population dynamics and targeted measures for health and life quality improving of the citizens of the Republic of Kazakhstan. Studies have revealed that the quality of life and health of the citizens of the Republic of Kazakhstan has improved. In recent years, the average life expectancy in Kazakhstan has exceeded 70 years. Economic growth has become stable. Today the world knows Kazakhstan as a peace-loving country, which stands for mutually beneficial cooperation and integration. Identified the necessary directions for further development, and conducted an analysis of the existing development programs of the Republic of Kazakhstan.
Keywords: demography; dynamics; Population Engineering; migration processes; population; recession; unemployment; marriage; family.